Implementasi Model Pembelajaran Project Based Learning Berbasis Kearifan Lokal dalam Meningkatkan Kreativitas Siswa Kelas VI MI At-Tanwir - Abidah, Mafruhatul (Program Studi Pendidikan Guru Madrasah Ibtidaiyah STAI Senori Tuban, 2025)
This study aims to enhance the creativity of sixth-grade students at MI Attanwir Bojonegoro through the implementation of a Project-Based Learning (PjBL) model integrated with local wisdom. In response to the demands of 21st-century skills, creativity is recognized as a key competency that should be nurtured from an early stage of education. However, teaching in elementary schools is still largely dominated by traditional lecture methods that offer limited student engagement. This research follows a Classroom Action Research (CAR) approach, conducted over two cycles with two meetings in each cycle, based on the Kemmis and McTaggart model. Data were collected through observation, interviews, and documentation, and analyzed using a descriptive-qualitative method. The findings reveal that the integration of PjBL with local cultural values significantly improved student creativity, as indicated by an increase in creativity indicators from 70% at the beginning to 85% by the end of the second cycle. Students became more enthusiastic, confident, and actively involved in learning, especially during culturally relevant art projects such as jumputan batik. These results suggest that a contextualized PjBL approach rooted in local wisdom can effectively foster students’ creative potential at the elementary level.